2011
DOI: 10.1007/s10530-011-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the establishment of invasive species: habitat and biotic interactions influencing the establishment of Bythotrephes longimanus

Abstract: Bythotrephes longimanus is an invasive pelagic crustacean, which first arrived in North America from Europe in early 1980s and can now be found throughout the Great Lakes and in many inland lakes and waterways. Determining the suitability of lakes to Bythotrephes establishment is an important step in quantifying its potential habitat range and environmental risk. Lake environmental conditions, planktivorous fishes, sport fishes and Bythotrephes occurrence data from 179 south-central Ontario lakes were used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Introducing competitive terms into habitat modeling can significantly increase the realism and precision of these models (Leathwick and Austin, 2001;Austin, 2002;Anderson et al, 2002;Wang and Jackson, 2011). However, it is difficult to estimate whether the current absence of a particular species is due to competition or to an unidentified environmental variable (Guisan and Thuiller, 2005;Elith and Leathwick, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Introducing competitive terms into habitat modeling can significantly increase the realism and precision of these models (Leathwick and Austin, 2001;Austin, 2002;Anderson et al, 2002;Wang and Jackson, 2011). However, it is difficult to estimate whether the current absence of a particular species is due to competition or to an unidentified environmental variable (Guisan and Thuiller, 2005;Elith and Leathwick, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this pattern has been confirmed by surveys that showed a relationship between the presence of Bythotrephes and high clarity (MacIsaac et al ., ; Branstrator et al ., ). Furthermore, in spite of not being the most important predictor of Bythotrephes establishment, statistical modelling has shown that DOC often emerges as one of the explanatory variables (Wang & Jackson, ). However , along the gradient of invasible lakes, our PCA results indicate that the effects of Bythotrephes on community composition in the darker lakes could be different than those observed in clearer lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Examining both the impacts of environmental factors and species interactions on species distributions is essential to understand how climate change, or other major environmental changes, will affect biodiversity. Many recent theoretical and empirical studies have demonstrated the importance of biotic interactions across large scales (Case et al ., ; Araújo & Luoto, ; Sexton et al ., ; Wang & Jackson, ; Wenger et al ., ; Bateman et al ., ; Kissling et al ., ; Wisz et al ., ). Understanding the role of biotic interactions in determining species distributions, however, is difficult and often hindered primarily by the availability of data and then by the difficulties in inferring causation, multicollinearity, the complexity of species interactions and spatial and temporal variation in those interactions (Wisz et al ., ; Svenning et al ., ).…”
Section: Introductionmentioning
confidence: 98%